MONITORING THE NUTRITIONAL STATUS OF TODDLERS WITH LILA RIBBONS IN DISASTER SITUATIONS IN CANDIPURO VILLAGE LUMAJANG - Paramita Viantry; Sa'bania Hari Raharjeng (UNUSA Press, 2022)
The impact of the eruption of Mount Semeru in Lumajang Regency, East Java, was in the form of environmental damage and caused many fatalities. The problem that needs to be addressed is related to the adequacy of nutrition for high-risk groups of people, including infants and toddlers, whose nutritional status and food intake are often not monitored. As an effort to overcome nutritional problems that arose after the eruption of Mount Semeru in Candipuro Village, Lumajang Regency. Monitor the nutritional status of toddlers aged 6-59 months who are at the evacuation site in Candipuro Village by measuring the Upper Arm Circumference (LiLA) using the Toddler LiLA tape and carried out for 1 month from the preparation stage, implementation to activity reporting. This Community Service activity was carried out at the Candipuro Village evacuation site with a target of 25 toddlers aged 6-59 months, and the results showed that the Toddler LiLA measurement that was carried out was declared successful because the toddlers whose nutritional status was monitored were confirmed to have good nutritional status while in the evacuation location. This activity is prioritized for toddlers because infants and toddlers are the most vulnerable group and require special nutritional treatment in the technical response to health crises due to disasters. It is stated that monitoring toddlers' growth must be carried out every month so that if toddlers experience nutritional problems, they can be handled more quickly and resolved.